Coordination Polymers Derived General Synthesis of Multishelled Mixed Metal‐Oxide Particles for Hybrid Supercapacitors. Issue 17 (28th February 2017) - Guan, Bu Yuan; Kushima, Akihiro; Yu, Le; Li, Sa; Li, Ju; Lou, Xiong Wen (David)
Abstract : Metal–organic frameworks (MOFs) or coordination polymers (CPs) have been used as precursors for synthesis of materials. Unlike crystalline MOF, amorphous CP is nonspecific to metal cation species, therefore its composition can be tuned easily. Here, it is shown that amorphous CP can be used as general synthesis precursors of highly complex mixed metal oxide shells. As a proof of concept, NiCo coordination polymer spheres are first synthesized and subsequently transformed into seven‐layered NiCo oxide onions by rapid thermal oxidation. This approach is very versatile and can be applied to produce ternary and quaternary metal oxide onions with tunable size and composition. The NiCo oxide onions exhibit exceptional charge storage capability in aqueous electrolyte with high specific capacitance (≈1900 F g −1 at 2 A g −1 ), good rate capability, and ultrahigh cycling stability (93.6% retention over 20 000 cycles). A hybrid supercapacitor against graphene/multishelled mesoporous carbon sphere shows a high energy density of 52.6 Wh kg −1 at a power density of 1604 W kg −1 (based on active materials weight), as well as remarkable cycling stability. Abstract : A general method is developed to synthesize highly complex multishelled mixed metal‐oxide particles with tunable size and composition from the pyrolysis of a novel class of amorphous coordination polymers. With the structural and compositional advantages, the unique seven‐shelled NiCo2 O4 particles exhibit remarkable electrochemical performance as an electrode material for hybrid supercapacitors.